Therapies for Chronic Spontaneous Urticaria: Present and Future Developments - Riccardo Asero; Paolo Calzari; Silvia Vaienti; Massimo Cugno (Pharmaceuticals)
Chronic spontaneous urticaria (CSU) is a complex dermatological condition characterized by recurrent wheals and/or angioedema lasting for more than six weeks, significantly impairing patients’ quality of life. According to European guidelines, the first step in treatment involves second-generation H1-antihistamines (sgAHs), which block peripheral H1 receptors to alleviate symptoms. In cases with inadequate responses, the dose of antihistamines can be increased by up to fourfold. If symptoms persist despite this adjustment, the next step involves the use of omalizumab, a monoclonal anti-IgE antibody, which has shown efficacy in the majority of cases. However, a subset of patients remains refractory, necessitating alternative treatments such as immunosuppressive agents like cyclosporine or azathioprine. To address these unmet needs, several new therapeutic targets are being explored. Among them, significant attention is being given to drugs that block Bruton’s tyrosine kinase (BTK), such as remibrutinib, which reduces mast cell activation. Therapies like dupilumab, which target the interleukin-4 (IL-4) and IL-13 pathways, are also under investigation. Additionally, molecules targeting the Mas-related G protein-coupled receptor X2 (MRGPRX2), and those inhibiting the tyrosine kinase receptor Kit, such as barzolvolimab, show promise in clinical studies. These emerging treatments offer new options for patients with difficult-to-treat CSU and have the potential to modify the natural course of the disease by targeting key immune pathways, helping to achieve longer-term remission. Further research is essential to better elucidate the pathophysiology of CSU and optimize treatment protocols to achieve long-term benefits in managing this condition. Altogether, the future of CSU treatments that target pathogenetic mechanisms seems promising.